PEMBERIAN SARI KURMA DAPAT MENINGKATKAN KADAR HB PADA IBU - Dainty Maternity; Auda Audrias; Dewi Yuliasari; Ana Mariza (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background Anemia in pregnancy is a maternal condition with hemoglobin values below 11 g/dl in the first and third trimesters, or hemoglobin levels less than 10 g/dl in the second trimester. Data on visits by pregnant women at Independent Practice Midwife Betty, Amd. Keb Based on a pre-survey conducted at BPS Okdiah Betty Amd. Keb Kec. Trimurjo Kab. Central Lampung, by looking at the visit data of pregnant women TM I-TM II for the last 3 months as many as 67 people, with the results of HB 8.0-10.0 examination with mild anemia category as many as 26 pregnant women (38.8%), and HB 10.1-13.0 with normal category as many as 14 people (20.9%), from the overall data it can be seen if there are 27 people (40.2 %) who did not do Hb checks during pregnancy. The purpose of this study was to determine the effect of giving date palm juice on increasing HB levels in pregnant women in the Independent Practice of Midwife Okdiah Betty, Amd. Keb Kec. Trimurjo Kab. Lampung in the middle of 2021..Methods This type of research is quantitative, the research design is pre-experimental method with a one group pretest - posttest design approach. Data on visits by pregnant women at Independent Practice Midwife Betty, Amd. Kec. Trimurjo Kab. Central Lampung, obtained the number of pregnant women TM I and III during the last 3 months as many as 67 people, purposive sampling technique., univariate and bivariate data analysis using t-testResult The average HB level in pregnant women before being given date palm juice with a mean of 10, 270gr/dl, a min value of 9.3gr/dl and a max value of 10.8gr/dl. The average Hb level at week 7 with a mean of 10.480gr/dl, a min value of 9.7gr/dl and a max value of 11.0gr/dl, and a Hb at week 14 with a mean of 10,807gr/dl, a min value of 10.2gr/dl and a max 11.2gr/dl. Conclusion there is an effect of giving date palm juice to increase Hb levels in pregnant women Suggestion Conducting outreach to the community as a form of promotional and preventive efforts to overcome and minimize the incidence of anemia. Keywords: Dates Extract, Hb Level, Pregnant Women ABSTRAK Latar Belakang Anemia dalam kehamilan merupakan suatu kondisi ibu dengan kadar nilai hemoglobin di bawah 11 gr/dl pada trimester satu dan tiga, atau kadar hemoglobin kurang dari 10 gr/dl pada trimester dua. Data Kunjungan ibu hamil di Praktik Mandiri bidanokdiah Betty, Amd. Keb Berdasarkan prasurvey yang dilakukan di BPS Okdiah Betty Amd.Keb Kec.Trimurjo Kab.Lampung Tengah, dengan melihat data kunjungan ibu hamil TM I-TM II selama 3 bulan terakhir sebanyak 67 orang,dengan hasil pemeriksaan HB 8,0-10,0 dengan kategori anemia ringan sebanyak 26 ibu hamil (38,8%),dan HB 10,1-13,0 dengan kategori normal sebanyak 14 orang (20,9%),dari data keseluruhan dapat diketahui jika terdapat 27 orang (40,2%) yang tidak melakukan pemeriksaan Hb saat hamil. Tujuan penlitian ini diketahuipengaruh pemberian sari kurma terhadap peningkatan kadar HB pada ibu hamildi Praktik Mandiri Bidan Okdiah Betty, Amd. Keb Kec.Trimurjo Kab.Lampung tengahtahun 2021..Metode Jenis penelitian kuantitatif, desain penelitian metode Pra Eksperimental dengan pendekatan one group pretest – posttest design. Data Kunjungan ibu hamil di Praktik Mandiri bidanokdiah Betty, Amd. Kec.Trimurjo Kab.Lampung Tengah, didapat jumlah ibu hamil TM I dan III selama 3 bulan terakhir sebanyak 67 orang, teknikpurposive sampling., analisa data univariat dan bivariat menggunakan t-testHasil Rata-rata kadar HB pada ibu hamilsebelum diberi sari kurma dengan Mean10, 270gr/dlnilai min 9,3gr/dl dan nilai max 10,8gr/dl.Rata-rata kadar Hb minggu ke 7 dengan Mean10,480gr/dlnilai min 9,7gr/dl dan nilai max 11,0gr/dl, dan Hb minggu ke 14 dengan Mean10,807gr/dlnilai min 10,2gr/dl dan nilai max 11,2gr/dl. Kesimpulan terdapat pengaruh pemberian sari kurma terhadap peningkatan kadar Hb pada ibuSaran Melakukan penyuluhan kepada masyarakat sebagai bentuk upaya promosi dan preventif untuk menanggulangi dan meminimalkan angka kejadian anemia. Kata Kunci : Sari Kurma, Kadar Hb, Ibu Hamil